PENGARUH CURRENT RATIO (CR) DAN DEBT TO ASSETS RATIO (DAR) TERHADAP NET PROFIT MARGIN (NPM) PADA PT. INDOCEMENT TUNGGAL PRAKARSA TBK TAHUN 2014 – 2023 - Fikri Wahyudin, Muhammad; Wartono, Tri (Journal of Research and Publication Innovation, 2024)
The purpose of this study was to determine the effect of Current Ratio and Debt To Assets Ratio on Net Profit Margin at PT Indocement Tunggal Prakarsa Tbk. This type of research is descriptive quantitative with the data analysis method used is descriptive statistics, Classical Assumption Test, Simple and Multiple Linear Regression Test, Correlation Coefficient Test, Determination Coefficient Test (R2 ) and Hypothesis Test (t test and f test) with the help of the SPSS version 26 program, with a significance level of 0.05 (5%) and the data source used is secondary data. The results of this study indicate that Current Ratio has an effect on Net Profit Margin. This can be seen from the test results which show that the tcount value is 7,010 > t table 2.364 at a significance level of <0.000. if 0.05 then H0 is accepted and Ha is rejected. Meanwhile, the Debt To Assets Ratio variable shows that the tcount is 4,458 > ttable 2,364 at the significance level <0.000. if 0.05 then H0 is accepted and Ha is rejected. This means that the debt to assets ratio affects the net profit margin. The results of the F test show that the current ratio and debt to assets ratio simultaneously have a significant effect on net profit margin. This can be seen from the Fcount value of 37,606 > Ftable 4.74 at a significance level of <0.000. If 0.05 then H0 is accepted and Ha is rejected. With a coefficient of determination of 0,891, it means that Net Profit Margin as the dependent variable is influenced by Current Ratio and Debt To Assets Ratio as independent variables (independent) by 89.1% and the remaining 10.9%, influenced by other variables not examined by researchers.